(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In this article, equality is a reflection of the qualities of social groups, people and what they own, that these qualities also represent number, quantity, volume, scope social equality is a relevant topic for each period and Generation, an idea kelshii and its philosophical and legal aspects are researched.